Pengaruh Nisbah Filler Abu Sawit (Ukuran Direduksi)/Carbon Black Dan Temperatur Pencampuran Terhadap Morfologi Dan Sifat Komposit Polipropilen/Karet Alam - S, Septiana Veronika; Bahruddin, Bahruddin; Fadli, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Fly ash (reducted particle size)/carbon black (CB) have been used as the main fillers that increase the quality of rubbers. As each filler possesses its own advantages, the use of fly ash (reducted particle size)/CB blends should enhance the mechanical properties of natural rubber (NR) vulcanizates. This research investigated the effect of blend ratio filler fly ash (reducted particle size)/carbon black and mixing temperature on morphology and mechanical properties of polypropylene (PP)/NR composite. Variation of blend ratio fly ash (reducted particle size)/CB at 0/100, 30/70, 50/50, 70/30 and 100/0 were studied in order to determine the optimum fly ash (reducted particle size)/CB ratio that giving rise to the optimum properties. The rubber compound has been made by two roll mill at ambient temperature and 20 rpm rotor speed. Dynamic vulcanization was done on internal mixer at various mixing temperature 175 oC, 180 oC , and 185 oC. Rotor speed on internal mixer at 60 rpm. The mechanical properties was done by Universal Testing Machine (UTM) and the morphology was examined by Scanning Electron Microscopy (SEM). The optimum result was found at fly ash (reducted particle size /CB ratio filler 30/70 and the optimum temperature was 175oC. The best mechanical properties was given on tensile strength 2,4 MPa, elongation at break 14,9 % and modulus elastic 71,6 MPa.Keywords: carbon black, fly ash, maleated natural rubber, natural rubber, polypropylene